Early-Onset Pectus Excavatum Is More Likely to Be Part of a Genetic Variation - Billar, Ryan; Heyman, Stijn; Kant, Sarina; Wijnen, René; Sleutels, Frank; Demirdas, Serwet; Schnater, J. Marco (European Journal of Pediatric Surgery, 2023)
Background Potential underlying genetic variations of pectus excavatum (PE) are quite rare. Only one-fifth of PE cases are identified in the first decade of life and thus are of congenital origin. The objective of this study is to test if early-onset PE is more likely to be part of genetic variations than PE that becomes apparent during puberty or adolescence.Materials and Methods Children younger than 11 years who presented with PE to the outpatient clinic of the Department of Pediatric Surgery at our center between 2014 and 2020 were screened by two clinical geneticists separately. Molecular analysis was performed based on the differential diagnosis. Data of all young PE patients who already had been referred for genetic counseling were analyzed retrospectively.Results Pathogenic genetic variations were found in 8 of the 18 participants (44%): 3 syndromic disorders (Catel–Manzke syndrome and two Noonan syndromes), 3 chromosomal disorders (16p13.11 microduplication syndrome, 22q11.21 microduplication syndrome, and genetic gain at 1q44), 1 connective tissue disease (Loeys–Dietz syndrome), and 1 neuromuscular disorder (pathogenic variation in BICD2 gene).Conclusion Early-onset PE is more likely to be part of genetic variations than PE that becomes apparent during puberty or adolescence. Referral for genetic counseling should therefore be considered.Trial Registration: NCT05443113
Keywords: surgery; chest anomaly; genetics; pediatrics